2011
DOI: 10.1002/jsfa.4710
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives to breed for improved baking quality wheat varieties adapted to organic growing conditions

Abstract: Northwestern European consumers like their bread to be voluminous and easy to chew. These attributes require a raw material that is rich in protein with, among other characteristics, a suitable ratio between gliadins and glutenins. Achieving this is a challenge for organic growers, because they lack cultivars that can realise high protein concentrations under the relatively low and variable availability of nitrogen during the grain-filling phase common in organic farming. Relatively low protein content in whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 91 publications
1
31
0
Order By: Relevance
“…For wheat development, the timing of N availability is very important as it affects the number of tillers, number of ears per tiller, number of grains per ear, thousand grain weight, and N concentration in the grains (Darwinkel 1978;Osman et al 2012). Although winter wheat can root deep (up to 2.0 m, see Table 1), the nutrients that accumulate in the grains need to be taken up during a crop stage when the nutrient uptake of the root system has already decreased (Spiertz and Ellen 1978).…”
Section: Crop Duration In Relation To Nitrogen Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…For wheat development, the timing of N availability is very important as it affects the number of tillers, number of ears per tiller, number of grains per ear, thousand grain weight, and N concentration in the grains (Darwinkel 1978;Osman et al 2012). Although winter wheat can root deep (up to 2.0 m, see Table 1), the nutrients that accumulate in the grains need to be taken up during a crop stage when the nutrient uptake of the root system has already decreased (Spiertz and Ellen 1978).…”
Section: Crop Duration In Relation To Nitrogen Demandmentioning
confidence: 99%
“…Osman et al (2012) argued that in order to increase grain N content in bread wheat, an increase in NUpE is more effective as increasing NUtE would decrease grain protein content. This last aspect was also noted by Barraclough et al (2010) and Górny et al (2011): they found a negative correlation between grain-NUtE and grain %N.…”
Section: Winter Wheatmentioning
confidence: 99%
“…Varieties with high quality protein and better nitrogen uptake were recommended for organic farming purposes by Osman et al (2012), as lower protein content was typically found at the organic sites. In the present experiment varieties were identified with high-quality protein, such as Lorenzo, Hendrix, Butaro, Montdor and Stefano (Table 5 and Figure 1 in Rakszegi et al 2016), which could be beneficial when growing them under organic conditions.…”
Section: Effect Of Breeding On the Variation And Performance Of The Vmentioning
confidence: 99%
“…The protein content was found to be lower at the organic site, so varieties with high-quality protein and better nitrogen uptake were recommended for oganic farming purposes to compensate for the relatively low protein content of the grain (Osman et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The effect of farming system on Zeleny test (49.67 ml in organic system, 50.37 ml in conventional one) was not statistically significant (Table 1). Several studies declare significantly lower protein content in grain of wheat grown in organic farming systems (Hildermann et al, 2009;Osman et al, 2011). The statistically significant but small difference in protein content between compared systems could be explained by the grown variety Balada that belongs to elite quality varieties of winter wheat.…”
Section: Resultsmentioning
confidence: 99%